EFL learners’ speaking development: asking referential questions - Bozorgian, Hossein; Fallah, Sakineh (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2017)
With the growing interest in interaction in EFL classes, referential questions play an important role in this regard. This study, a quasi-experimental pretest and posttest design, aims at investigating the effect of asking referential questions on the oral production of a group of lower intermediate male students (N = 16) who were learning English in Iran. The students’ performance in pretest and posttest was audio-recorded, and then by listening to the students’ voice by the experimental group teacher, the number of words produced by every student in pretest and posttest was counted. The time during which the students talked about the topics before and after asking referential questions was also calculated in minutes. The results reveal that: (i) asking referential questions increased talk time and number of words produced by the learners and therefore improved their speaking ability, and (ii) the students in experimental group produced more words and talked longer than the students in control group. In conclusion, the finding of this study suggests that particular types of questions, called referential questions, increase learners’ oral proficiency in classroom.